2015
DOI: 10.1103/physrevc.92.014910
|View full text |Cite
|
Sign up to set email alerts
|

Tomography of the quark-gluon plasma by charm quarks

Abstract: We study charm production in ultra-relativistic heavy-ion collisions by using the Parton-Hadron-String Dynamics (PHSD) transport approach. The initial charm quarks are produced by the Pythia event generator tuned to fit the transverse momentum spectrum and rapidity distribution of charm quarks from Fixed-Order Next-to-Leading Logarithm (FONLL) calculations. The produced charm quarks scatter in the quark-gluon plasma (QGP) with the off-shell partons whose masses and widths are given by the Dynamical Quasi-Parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
171
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 160 publications
(188 citation statements)
references
References 88 publications
9
171
4
Order By: Relevance
“…The hadronized D−mesons then interact with light hadrons in the hadronic phase until freeze out and subsequently undergoes semileptonic decay. We have found that the PHSD approach, which has been applied for charm production in Au+Au collisions at √ s NN =200 GeV [29] and in Pb+Pb collisions at √ s NN =2.76 TeV [30], describes the R AA as well as the v 2 of D−mesons in reasonable agreement with the experimental data from the STAR collaboration [33,34] and from the ALICE collaboration [35,36] when including the initial shadowing effect in the latter case.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…The hadronized D−mesons then interact with light hadrons in the hadronic phase until freeze out and subsequently undergoes semileptonic decay. We have found that the PHSD approach, which has been applied for charm production in Au+Au collisions at √ s NN =200 GeV [29] and in Pb+Pb collisions at √ s NN =2.76 TeV [30], describes the R AA as well as the v 2 of D−mesons in reasonable agreement with the experimental data from the STAR collaboration [33,34] and from the ALICE collaboration [35,36] when including the initial shadowing effect in the latter case.…”
Section: Introductionsupporting
confidence: 73%
“…We employ the PYTHIA event generator to produce the heavy-quark pairs and modify their transverse momentum and rapidity such that they are similar to those from the FONLL calculations [32]. In case of p+p collisions at the top RHIC energy of √ s = 200 GeV, the transverse momentum and the rapidity of the charm quark from the PYTHIA event generator are reduced by 10 % and 16 % [29], respectively, and those of the bottom quark are unmodified. The transverse momentum of charm quarks at the invariant energy of √ s = 62.4 GeV is modified to p * T = p T − 0.6 tanh(p T /1.2 GeV), where p T and p * T , respectively, are the original and modified transverse momenta, while the rapidity is reduced by 15 % [32].…”
Section: Single Electrons From Heavy Flavor In P+p Collisionsmentioning
confidence: 99%
See 3 more Smart Citations